Exploring the relationships between housing, neighbourhoods and mental wellbeing for residents of deprived areas - Bond Lyndal; Kearns Ade; Mason Phil; Tannahill Carol; Egan Matt; Whitely Elise (BMC, 2012)
Abstract Background Housing-led regeneration has been shown to have limited effects on mental health. Considering housing and neighbourhoods as a psychosocial environment, regeneration may have greater impact on positive mental wellbeing than mental ill-health. This study examined the relationship between the positive mental wellbeing of residents living in deprived areas and their perceptions of their housing and neighbourhoods. Methods A cross-sectional study of 3,911 residents in 15 deprived areas in Glasgow, Scotland. Positive mental wellbeing was measured using the Warwick-Edinburgh Mental Wellbeing Scale. Results Using multivariate mulit-nomial logistic regressions and controlling for socio-demographic characteristics and physical health status, we found that several aspects of people's residential psychosocial environments were strongly associated with higher mental wellbeing. Mental wellbeing was higher when respondents considered the following: their neighbourhood had very good aesthetic qualities (RRR 3.3, 95% CI 1.9, 5.8); their home and neighbourhood represented personal progress (RRR 3.2 95% CI 2.2, 4.8; RRR 2.6, 95% CI 1.8, 3.7, respectively); their home had a very good external appearance (RRR 2.6, 95% CI 1.3, 5.1) and a very good front door (both an aesthetic and a security/control item) (RRR 2.1, 95% CI 1.2, 3.8); and when satisfaction with their landlord was very high (RRR 2.3, 95% CI 2.2,4.8). Perception of poor neighbourhood aesthetic quality was associated with lower wellbeing (RRR 0.4, 95% CI 0.3, 0.5). Conclusions This study has shown that for people living in deprived areas, the quality and aesthetics of housing and neighbourhoods are associated with mental wellbeing, but so too are feelings of respect, status and progress that may be derived from how places are created, serviced and talked about by those who live there. The implication for regeneration activities undertaken to improve housing and neighbourhoods is that it is not just the delivery of improved housing that is important for mental wellbeing, but also the quality and manner of delivery.